PERILAKU KONSUMEN VEGETARIAN DI SAMARINDA DAN STRATEGI PENGEMBANGAN - Willyamto Sutardjo Liu (Jurusan Ilmu Ekonomi Prodi Ekonomi Pembangunan Fakultas Bisnis dan Ekonomika Universitas Surabaya, 2017)
This study aims to examine consumer behavior, customer satisfaction and development strategies that can support or hinder the development of vegetarian restaurants Fortunate Coffee using SWOT analysis. Research with qualitative approach using an analytical process begins with a browse through all the data available from the following sources using literature study, internet media, interviews, and questionnaires.Findings from this study showed that a vegetarian restaurant Fortunate Coffee has many advantages that can support the development of, among other strategic place and cozy, reasonable prices, good service, taste the food was pretty good, and have the product in Samarinda recently sold in Fortunate Coffee vegetarian restaurant that is Bread Vegan. Through of the findingsstrength, weakness, opportunity, threats, then difomulasikan into the SWOT matrix and eventually found a few strategies, namely strategies SO (strength-opportunity) flavorenhancing its menu. ST Strategy (strength-threats) maintain selling prices to remain stable. WO Strategy (weakness-opportunity) held activities such as seminars vegetarian and exciting events. WT Strategy (Weakness-threats), an improvement in consumer promotions, the need for special training to waiters in service procedures, innovations in the form of home delivery.